Mobility for university studies in the new city Ali Mendjeli. Reading and analysis of movement flows - ACHERARD, Sabrina; BOUKERZAZA , Hosni (Journal of Human Sciences, 2020)
The main objective of this paper is to study the mobility for university studies in the new city Ali Mendjeli. The work consists of reading and analyzing the different movement flows for the study motive, practiced within the territory of the city. It is based on the exploitation of data relating to the geographical origins of students from their places of residence and available in the various academic departments of the universities of the wilaya of Constantine.      The analysis reveals several original results which inform us not only about the volume and directions of the flows, but especially on the scales and the organization of displacements.      The work submitted should stimulate more advanced works on mobility and encourage good flow management in order to improve the mobility conditions for the entire population of the city and for students in particular.